2018
DOI: 10.1039/c7ra12672g
|View full text |Cite
|
Sign up to set email alerts
|

Clear transparent cellulose nanopaper prepared from a concentrated dispersion by high-humidity drying

Abstract: Optically transparent cellulose nanopaper is a promising candidate for flexible device substrates because of its light weight, surface smoothness, and high dimensional stability with respect to temperature.Conventionally, clear transparent nanopaper has been fabricated from cellulose nanofiber dispersions with quite low concentration: less than 0.5 wt%. However, this diluteness leads to several problems, such as huge energy consumption and long operation time for drying. Therefore, nanopaper should be fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…When the concentrations of the dispersions with different initial concentrations of 1.3–1.6 wt % were diluted to 0.2 wt % and then subjected to oven drying, the nanopaper haze was reduced by 20–30%, regardless of alkali-treatment, compared with the values of nanopapers prepared without dilution ( Figure 3 a–c). However, as previously reported by Isobe et al, these nanopapers were still hazy translucent even after the water dilution [ 22 ], because the high-concentration dispersions without dilutions produced translucent nanopaper with haze values of approximately 30%. Moreover, when the concentration of the dispersion was diluted from 2.0 to 0.2 wt %, the haze of the nanopaper slightly increased rather than decreasing ( Figure 3 d).…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…When the concentrations of the dispersions with different initial concentrations of 1.3–1.6 wt % were diluted to 0.2 wt % and then subjected to oven drying, the nanopaper haze was reduced by 20–30%, regardless of alkali-treatment, compared with the values of nanopapers prepared without dilution ( Figure 3 a–c). However, as previously reported by Isobe et al, these nanopapers were still hazy translucent even after the water dilution [ 22 ], because the high-concentration dispersions without dilutions produced translucent nanopaper with haze values of approximately 30%. Moreover, when the concentration of the dispersion was diluted from 2.0 to 0.2 wt %, the haze of the nanopaper slightly increased rather than decreasing ( Figure 3 d).…”
Section: Resultssupporting
confidence: 61%
“…Inhomogeneous aggregations in cellulose nanofiber dispersions from holocellulose pulp without alkali-treatment are known to disintegrate upon water dilution [ 22 ]. When the concentrations of the dispersions with different initial concentrations of 1.3–1.6 wt % were diluted to 0.2 wt % and then subjected to oven drying, the nanopaper haze was reduced by 20–30%, regardless of alkali-treatment, compared with the values of nanopapers prepared without dilution ( Figure 3 a–c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of great significance for transparency, and it can be altered according to the process by which nanocellulose films are manufactured. Isobe et al (2018) and Kasuga et al (2018) reported that the haze of a nanocellulose film prepared by cast drying a wood-derived holocellulose pulp increased as the initial concentration of the nanocellulose suspension increased. Cast drying in a highhumidity environment markedly lowers the haze, and drying slowly in a humid environment produces low-haze films.…”
Section: Light Manipulation By Nanocellulosementioning
confidence: 99%
“…Compared with traditional transparent substances, such as glass and plastic films, nanopaper is a unique transparent material because it has hierarchical structures in which cellulose molecule chains form crystalline CNFs, which aggregate or align to form macroscopic nanopaper. This hierarchy, however, causes a problem-the optical properties of the nanopaper, including the transparency or haze, vary due to the various drying processes affecting CNF alignment [14][15][16]. For example, the transparency of nanopapers prepared by the evaporation-condensation method and vacuum filtration, followed by hot pressing, are substantially different [14].…”
Section: Introductionmentioning
confidence: 99%